PENGARUH LINGKUNGAN KERJA POSITIF TERHADAP INTERAKSI SOSIAL KARYAWAN - Marlina, Lenny; Wahyu Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The work environment plays a crucial role in determining employee effectiveness and productivity. A positive work environment not only impacts individual performance but also affects social interactions among employees. Good social interaction can improve collaboration, communication and team cohesiveness which in turn can contribute to a more harmonious and productive work atmosphere. However, factors such as work pressure, lack of communication, and unsupportive organizational culture often hinder relationships between employees. The purpose of this study is to assess how a positive work environment can contribute to social interaction among employees. By understanding this relationship, it is hoped that companies can develop more effective strategies to create a work environment that is not only productive, but also harmonious. This is important for improving individual and team performance, as well as creating a better work culture within an organization. The research method used is a qualitative method with interview and group discussion techniques to collectively explore employees' views on the work environment and its relationship with social interaction. Then select one educational institution that has a positive work environment and analyze its impact on social interaction in it. The results of this study show that there is a significant positive relationship between a positive work environment and the level of social interaction. Employees who work in a supportive environment, such as open communication and management support show higher levels of social interaction.